2022
DOI: 10.3390/nu14245250
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity in the Rural United States: An Examination of Struggles and Coping Mechanisms to Feed a Family among Households with a Low-Income

Abstract: Households with a low-income in rural places experience disproportionate levels of food insecurity. Further research is needed about the nuances in strategies that households with a low-income in rural areas apply to support food security nationally. This study aimed to understand the barriers and strategies that households with a low-income in rural areas experience to obtain a meal and support food security in the United States. We conducted a qualitative study with semi-structured interviews among 153 prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
(64 reference statements)
0
7
1
Order By: Relevance
“…This aligns with a recent report highlighting that food insecurity was most prevalent in principal cities located within large urban areas compared to rural areas [ 43 ]. Nevertheless, this finding is contrary to some previous research findings [ 44 , 45 , 46 ], revealing that children living in rural areas have higher rates of food insecurity than children living in urban areas. However, it is also important to note that the difference in food insecurity status between urban and rural children was not statistically significant after controlling for other factors, such as household income and race/ethnicity.…”
Section: Discussioncontrasting
confidence: 99%
“…This aligns with a recent report highlighting that food insecurity was most prevalent in principal cities located within large urban areas compared to rural areas [ 43 ]. Nevertheless, this finding is contrary to some previous research findings [ 44 , 45 , 46 ], revealing that children living in rural areas have higher rates of food insecurity than children living in urban areas. However, it is also important to note that the difference in food insecurity status between urban and rural children was not statistically significant after controlling for other factors, such as household income and race/ethnicity.…”
Section: Discussioncontrasting
confidence: 99%
“…A qualitative study among food insecurity experts suggested that although the high cost of nutrient-rich foods is a barrier encountered by SNAP participants, enhancing nutrition education with more flexible formats (e.g., point -of-purchase prompts like recipe demonstrations) in tandem with incentives may lead to greater impact when compared with programs offering incentives alone [ 39 ]. It is also important to acknowledge that not all individuals with a low income want or need traditional/didactic nutrition education, affordability is the most limiting factor to a healthy diet, and other supports can help [ 5 , 7 , 9 , [10] , [11] , 40 ]. For instance, another NTAE case study reported that many NI grantees also provide participants with assistance in navigating incentive earning and redemption, as a part of nutrition education [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of participants are Latinx and participated in at least one federal food assistance program. The implications of food insecurity in rural communities are under-researched (Byker Shanks et al, 2022). Although rates of food insecurity in rural areas mimic rates in urban areas (Coleman-Jensen et al, 2020), communities with the highest prevalence of food insecurity are disproportionately rural (Hake et al, 2022).…”
Section: Samplementioning
confidence: 99%